2015
DOI: 10.1016/j.jpain.2015.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Out-Of-Pocket Expenditures on Complementary Health Approaches Associated With Painful Health Conditions in a Nationally Representative Adult Sample

Abstract: National surveys suggest that millions of adults in the United States use complementary health approaches such as acupuncture, chiropractic manipulation, and herbal medicines to manage painful conditions such as arthritis, back pain and fibromyalgia. Yet, national and per person out-of-pocket (OOP) costs attributable to this condition-specific use are unknown. In the 2007 National Health Interview Survey, use of complementary health approaches, reasons for this use, and associated OOP costs were captured in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 40 publications
1
41
0
1
Order By: Relevance
“…26 Also, non-pharmacological treatments that are potentially efficacious for reducing pain’s impact (e.g., mindfulness training) 6 may not be covered by insurance, placing such therapies out of reach for many older Americans. 28 Among older adults with any chronic pain, almost half of individuals in the lowest wealth quartile, and 35% of African Americans, reported that pain impacted their ability to “pay for needs”–suggesting that even in a population largely insured through Medicare, chronic pain presents a financial hardship.…”
Section: Discussionmentioning
confidence: 99%
“…26 Also, non-pharmacological treatments that are potentially efficacious for reducing pain’s impact (e.g., mindfulness training) 6 may not be covered by insurance, placing such therapies out of reach for many older Americans. 28 Among older adults with any chronic pain, almost half of individuals in the lowest wealth quartile, and 35% of African Americans, reported that pain impacted their ability to “pay for needs”–suggesting that even in a population largely insured through Medicare, chronic pain presents a financial hardship.…”
Section: Discussionmentioning
confidence: 99%
“…7, 8, 10, 11, 14 In 2007, for example, about 14.3 million adults used a complementary health approach for their back pain, while about 5.0 million used these approaches for their neck pain, and 3.1 million for their arthritis. 7 Far fewer individuals used complementary health approaches for other chronic diseases such as depression (1.0 million), hypertension (0.8 million), diabetes (0.7 million) or cancer (0.4 million).…”
Section: Introductionmentioning
confidence: 99%
“…Based on national survey data, 14 this high use of complementary health approaches for painful conditions translated into $8.5 billion out-of-pocket for these approaches to manage back pain, $3.6 billion to manage neck pain, and $2.3 billion to manage arthritis. Substantially less is spent out-of-pocket on complementary health approaches to treat other chronic health conditions such as depression ($1.1 billion), hypertension ($0.7 billion), diabetes ($0.3 billion), and cancer ($0.2 billion).…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, a study found that the most popular CAM providers in Canada were chiropractors (40% of Canadians use during their lifetimes), acupuncturists (17%), naturopaths (9%) and homeopaths (9%) 2. American data suggest that in 2012 Americans spent ∼$30.2 billion on CAM, with adults spending an average of $514 on CAM practitioner visits, supplements and self-care approaches 3. CAM clinics are abundant in each major Canadian metropolitan centre and many of those clinics engage in advertising online.…”
Section: Introductionmentioning
confidence: 99%